Temperature dependence of current-induced magnetic domain wall motion in an asymmetric Co/Ni nanowire. (6th February 2015) - Ueda, Kohei; Hiramatsu, Ryo; Kim, Kab-Jin; Taniguchi, Takuya; Tono, Takayuki; Moriyama, Takahiro; Ono, Teruo
Abstract: We have investigated the temperature dependence of current-induced magnetic domain wall (DW) motion in a Co/Ni nanowire, where the spin Hall torque is responsible for the DW motion. The threshold current density ( J th ) for DW motion is found to be dependent on the temperature T and the depinning magnetic field H dep, which is different from the symmetric Co/Ni system where J th is insensitive to T and H dep . This result indicates that an extrinsic pinning governs the DW motion when it is driven by the spin Hall torque. Our work therefore suggests that reducing the extrinsic pinning is a key for achieving a low-power-consumption device.